Colposcopy and Cervical Pathology - Rajkumar, Rajamanickam (IntechOpen, 2017)
This book entitled Colposcopy and Cervical Pathology is the third successful book of the editor with InTech publishers. This book serves the purpose of providing, valuable and valid, innovative ideas/suggestions for utilizations of the "resource-rich/resource-intensive" colposcopy and cervical pathology technology in a "cost-/resource-effective" way by the health providers and planners, especially in "resource-limited/resource-poor settings." Transfer of technology from high- to low-resource settings in all the programs of preventive/community oncology services, across the world, is highly recommended and strongly advocated. The authors have well contributed to the goal of advanced science being made accessible for the benefit of common man. The InTech publishers have the distinct honor of imbibing the in-depth knowledge and vast experiences from experts of international repute and infusing it to the health providers and planners of developing countries, so that the communities of all nations are richly benefited. The book is a pearl, which deserves a precious and purposeful planning model for achieving "global health by education and empowerment."